Structural Abnormalities of Spermatozoa in Triploid Gynogenetic Crucian Carp (Carassius auratus) - He, Wangchao; Sun, Yu; Qiang, Jiaxu; Luo, Xinyue; Zhang, Hui; Yang, Conghui; Luo, Kaikun; Zhao, Rurong; Qin, Qinbo; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2021)
The spermatozoa of triploid gynogenetic crucian carp (Carassius auratus) (3nDTCC) possess spermatogenesis completely process with normal genetic background. However, the genetic materials of these spermatozoa do not inherit in gynogenetic progeny. Understanding the intrinsic mechanism may helpful for developing breeding strategies of gynogenetic fishes. In this study, the spermatozoa ultrastructure of diploid red crucian carp and 3nDTCC, was systematically studied to demonstrate their cytological structural differences. In addition, the artificial breeding tests of 3nDTCC(♀) with different ploidy spermatozoa were performed to verify the contributions of genetic materials from 3nDTCC spermatozoa to the gynogenesis progeny. Furthermore, the mRNA expression of centriole related genes (i.e., cep57, cetn1, rootletin and nek2) involved in spermatozoa packaging were also determined by quantitative real-time PCR (qPCR) to illustrate the molecular expression characteristics of spermatozoa packaging process in 3nDTCC. The results reveal the adaptive features of spermatozoa in 3nDTCC, including loose midpiece structure, abnormal head structure and abnormal expression of centriole related genes, which may influence the motility of spermatozoa and make it not involved in the genetic composition of the gynogenesis offspring.